Extraction of carbon dots from empty fruit bunch biochar via an acid-free hydrothermal method - Jamaludin, Norhanisah; Abdul Rashid, Suraya; Tan, Tong Ling (2018)
Carbon dots (CD) have attracted tremendous attention due to its characteristics of good stability, excellent optical properties and low toxicity. Generally, we discuss a facile hydrothermal method in extracting CD from empty fruit bunch (EFB) biochar. The obtained CD was characterized by UV-visible spectroscopy, photoluminescence spectroscopy (PL) and High-resolution electron microscopy (HRTEM). Under a UV light, the extracted CD exhibits a blue luminescence with maximum absorption and emission peak of 348 nm and 430 nm respectively. The TEM images showed CD shape to be nearly spherical and monodispersed with an average diameter of 4.6 nm and lattice spacing of 0.21 nm. The result obtained suggest that the CD could possibly be utilized for further application.